The Psychopath Phenomenon Reflected In Karen Rose's Nothing To Fear Novel (2005): A Psychoanalytic Approach - Utomo, Danang Budi Mulyo, Dr. M. Thoyibi, M.S, Mauly Halwat Hikmat, Ph. D (2014)
This research aims at analyzing the psychopath phenomenon reflected by Sue Conway by using Psychoanalytic Approach. The major problem in this research is how Sue expresses her psychopath by killing her enemies without remorse and does everything for her goal reflected in Karen Rose's nothing to fear. The research consists of two objectives: analyzing the novel based on structural elements and analyzing the novel based on Psychoanalytic Approach. This study uses qualitative research. The object of the study is Nothing to Fear novel written by Karen Rose's. There are two kinds of data source primary and secondary. The primary data source is the text of the novel Karen Rose's Nothing to Fear and the secondary data sources are some books and articles related to the subject. The method of collecting data in the research is library research by summarizing, paraphrasing, and documenting the data. In analyzing the data, the writer applies descriptive analysis. The results of the research are as follows, based on psychoanalytic analysis, the main character, Sue Conway is a woman who has a steel-minded person, does not despair and have strong desire. Second, vengeance is necessary for Sue to restore her self-esteem and to punish their enemies in order to make them aware of their mistakes. Last, Rose writes the Nothing to Fear novel as anyone can be psychopath. Because psychopath lives in every people, sometimes we realize and sometimes not. Beware, psychopaths exist and they are around us.